Growth of TiO2 nanotubes by anodization of Ti-7.5Mo in NH 4F solutions - Escada, A. L A [UNESP]; Nakazato, R. Z. [UNESP]; Claro, A.P.R. Alves [UNESP] (American Scientific Publishers, 2013)
Titanium and its alloys are widely used as biomaterials due to their mechanical, chemical and biological properties. To enhance the biocompatibility of titanium alloys, various surface treatments have been proposed. In particular, the formation of titanium oxide nanotubes layers has been extensively examined. According to the literature, it is possible to induce the growth of TiO2 on the surface of titanium, employing the aqueous anodizing electrolyte. This Ti-7.5Mo alloy was anodized in glycerol electrolytes containg 0.25 wt% of NH4F, with variations in time, voltage and calcinations temperature. After anodization, the sample surfaces were analyzed with a field emission scanning electron microscopy, DRX and contact angle measurements. It was possible to observe the formation of TiO2 on the surface and these findings represent a simple surface treatment for Ti alloys that has high potential for biomedical applications. Copyright © 2013 American Scientific Publishers. All rights reserved.
Keywords: Anodization; TiO2 nanotubes; Titanium alloys; Anodizations; Biomedical applications; Calcinations temperature; Chemical and biologicals; Field emission scanning electron microscopy; Glycerol electrolyte; TiO; Titanium oxide nanotubes; Anodic oxidation; Biocompatibility; Biological materials; Contact angle; Electrolytes; Field emission microscopes; Medical applications; Nanotubes; Surface treatment; Titanium; Titanium dioxide